Producer and Consumer Behavior towards the Consumption of Halal Food and Beverages - Rizqa, Agitsna Alya; Afandi, Mukhamad Yazid (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2024)
Introduction: Indonesia, as a country with a majority Muslim population, shows its concern for religion by consuming halal food and beverage products. Balanced consumption in Islam is implemented by avoiding tabzir and israf behavior. Objective: The method used is literature with qualitative data to describe community behavior from the producer and consumer sides when considering daily halal food and beverages. Method: The research approach used is a comparative qualitative approach. The research data was obtained from risk management reports contained in the annual reports of Bank Victoria Syariah and Bank Syariah Indonesia in 2023. Result: The result of this study is that consumers still think that halal food and beverages are only based on whether the product contains pork and dog meat and their derivatives or not. The obstacles from related agencies are moving institutions and processes that are still confusing and centralized, so there is a lack of human resources. Producer constraints are related to high costs, business management unpreparedness, and lack of socialization and awareness to register their products. Business actors' fraud against the halal label cannot be handled seriously with the policy of the halal product guarantee agency. Implication: This study increases awareness and adherence to halal standards among the public, including producers, consumers, and related institutions.